Analysis of engine performance with enhanced fuel - Ihsan, Sany Izan; Farid, Khairussani; Mel, Maizirwan; Mohiuddin, A. K. M. (IIUM Press, 2011)
The performance of an ordinary automobile engine was tested with several percentage of industrially made ethanol (99.8%) mixed with gasoline in IIUM Engine Test Bed. Without having any modification to the engine, a 1500 cc. Mitsubishi 4G 15 internal combustion four engine was tested with various percentages of ethanol mixed with gasoline starting trom 5%, 15%, 25% and 35%. The results show that by increasing the percentage of ethanol in the fuel, the engine can have more power as well as higher efficiency with low specific fuel consumption (SFC). The gas emission analysis also recorded that having more ethanol in gasoline will reduce the emission of some hazardous gases from the engine combustion compared to gasoline only fuel.